Stochastic linear programming models, theory, and computation - Kall Peter; Mayer Janos (New York Springer-Verlag, 2005)
It is a definitive presentation and discussion of the theoretical properties of the models, the conceptual algorithmic approaches, and the computational issues relating to the implementation of these methods to solve problems that are stochastic in natur
Keywords: Linear programming; Stochastic linear programming